Religion and national identity : governing Scottish Presbyterianism in the eighteenth century - Mutch, Alistair, 1954- (Edinburgh University Press, 2015)
Presbyterianism has shaped Scotland and its impact on the world. Behind its beliefs lie some distinctive practices of governance which endure even when belief fades. These practices place a particular emphasis on the detailed recording of decisions and what we can term a 'systemic' form of accountability. This book examines the emergence and consolidation of such practices in the eighteenth century Church of Scotland. Using extensive archival research and detailed local case studies, it contrasts them to what is termed a 'personal' form of accountability in England in the same period. This supports the contrast that has been made by other authors between a focus on system in Scotland, character in England. The wider impact of this approach to governance and accountability, especially in the United States of America, is explored, as is the enduring impact of these practices in shaping Scottish identity. This book offers a fresh perspective on the Presbyterian legacy in contemporary Scottish historiography, at the same time as informing current debates on national identity. Key Features:. A novel focus on religion as social practice, as opposed to belief or organization A strong focus on Scotland, but in the context of Britain Extensive archival work in the Church of Scotland records, with an emphasis on form as well as content A different focus on the Church of Scotland in the eighteenth centuryOffers a detailed focus on local practice in the context of national debates